Quality of life of people with Parkinson's disease in the context of professional work and physiotherapy - Joanna Cholewa; Agnieszka Gorzkowska; Agnieszka Nawrocka; Jarosław Cholewa (Nofer Institute of Occupational Medicine, 2017)
Background: Of many diseases and disorders of the nervous system Parkinson's disease (PD) deserves a particular attention for its specific effects having an impact on the ability to undertake different forms of professional and economic activities. Due to the constantly growing incidence rate and the lowering age of patients, PD is becoming more and more serious social problem. The aim of this study was to determine the effects of professional work and physiotherapy on the quality of live in people with Parkinson's disease. Material and Methods: The research was carried out on 109 people with diagnosed PD of stage II according to the Hoehn and Yahr classification. They were divided into professionally working and non-working subjects and those participating and not participating in physiotherapy programs. The Unified Parkinson's Disease Rating Scale (UPDRS), was used to estimate the patients' clinical status. The Parkinson's Disease Questionnaire (PDQ-39), the Quality of Life Short Form (SF-36) Questionnaire and the Parkinson's Disease Quality of Life Questionnaire (PDQL) were used to estimate the quality of life. Results: In all groups statistically significant differences were observed in each of the used scale. The PDQ-39 (F = 5.278, p = 0.04), SF physical component (F = 4.24, p = 0.005), SF mental component (F = 3.45, p = 0.021), PDQL (F = 6.57, p = 0.003). The highest quality of life was noticed in people working professionally and participating in physiotherapy programs. Conclusions: Professional activity and participation in properly planned physiotherapy help reduce the symptoms and improve the quality of life of people with Parkinson's disease. The study showed that the quality of life of people with PD is determined by professional work and participation in the process of rehabilitation. Med Pr 2017;68(6):725-734